Quasi-elastic deformation with rebound resilience in bulk amorphous Al2O3–ZrO2–Y2O3 at moderate temperature. Issue 18 (15th December 2020) - Wei, Ding; Xu, Xiqing; Wang, Yanli; Chen, Xin; Gan, Yundan; Li, Hui; Wang, Xingang
Abstract: Large quasi-elastic deformation with high degree of rebound resilience was reported in dense, monolithic ceramics for the first time, which was achieved in the cyclic compression-resilience tests on bulk amorphous Al2 O3 –ZrO2 –Y2 O3 at 600 °C. As the compression strain was 4%, the resilience ratios in the three cycles were 89.5%, 100% and 100%, respectively; for compression strain of 8%, the resilience ratios were 74.5%, 90.6% and 92.0%. The superior elastic deformation in amorphous Al2 O3 –ZrO2 –Y2 O3 was due to the round trip migration of atoms through free volume in amorphous phase, and the residual strain after deformation of 4% and 8% are resulted from structural densification and shear band formation, respectively. This work could inspire new guidance on elastic deformation in ceramics, and provide new guidance to ceramic materials with high elastic deformation and rebound resilience in engineering applications.